Importance of Work Motivation and the Culture of the Company to Improve Organizational Citizenship Behavior - Muh. Nasir Hamzah; Munawir Nasir; Muliyadi Hamid; Mujahid Mujahid (Universitas Mercu Buana, 2022)
Objectives: The research aims to find out if job motivation and organizational culture affect the development of organizational citizen behaviors (OCBs) through employee performance.Methodology: The research was conducted in one of Gorontalo Province’s, with a population of 2,262 employees, and questionnaires were distributed to 260 employees in various departments who volunteered to be respondents; sampling was based on Slovins Formula. Processing data with Structural Equation Model (SEM) and AMOS.Finding: The findings indicated that motivation affected employee performance, organizational culture did not affect performance, motivation had no effect on OCB, organizational culture had no effect on OCB, and employee performance had no effect on organizational culture's influence on OCB.Conclusion: These findings can be explained by the fact that the work incentive used thus far is intrinsic, providing encouragement and inspiration for all employees to improve performance. Organizational culture has not affected employee performance, indicating that the organizational culture employed thus far has been result-oriented and ineffectively applied.